Determination of Mobile Technology Use in an Interactive Distance Education Classroom Environment - Begaliyeva, Saule B.; Ospanova, Bakhytzhan; Magauova, Akmaral; Koshkimbayeva, Raissa; Manyapova, Tina; Aubakirova, Rakhila Zh (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The aim of this study is to investigate the determination of university students’ use of mobile technology in an interactive distance education classroom environment. The quantitative research method was used in the research. The research was conducted in the fall semester of 2021–2022. A total of 318 university students continuing their education in Kazakhstan voluntarily participated in the research. In the research, a 4-week online training was given to university students. The ‘distance education and mobile technology’ measurement tool developed by the researchers and compiled by experts in the field was used. The measurement tool was delivered and collected by university students via the online method. The analysis of the data was made by using the SPSS programme, frequency analysis, t-test and analysis of variance (ANOVA) test, and the results were added to the research in the form of tables. According to the results obtained from the research, it has been concluded that while university students’ level of knowledge in terms of distance education and mobile technologies is high, the situation of university students not using mobile technologies is quite low, but the rate of using them very often is quite high; and it is used by reflecting on the distance education systems in the course.